1990
DOI: 10.1149/1.2086199
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Gaseous Species in the Sodium‐Scandium‐Iodine System

Abstract: The vaporization behavior of NaI(s), ScI3(s), and mixtures of these two phases containing 50, 92, 95, and 98 mole percent (m/o) NaI has been studied by effusion-beam mass spectrometry and by torsion-mass-effusion techniques in the approximate region 700-900 K. Vapor molecular weights show that NaI and SCI3 monomers make up 84 and 94 m/o, respectively, of the saturated vapors over the pure phases with the balance primarily dimer. NaScI4 is the maj or gaseous species over the mixtures, with a small amount of Na2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Chemical modeling of local equilibrium conditions is a useful tool in predicting lamp behavior, and for this reason studies of the vaporization thermodynamics of the NaBr−DyBr 3 1 and NaI−DyI 3 2,3 systems have been reported. Similar studies of the NaI−ScI 3 system have also been reported. , In addition, Hilpert 6 has reviewed much of the information on complexation of metal halide vapors.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Chemical modeling of local equilibrium conditions is a useful tool in predicting lamp behavior, and for this reason studies of the vaporization thermodynamics of the NaBr−DyBr 3 1 and NaI−DyI 3 2,3 systems have been reported. Similar studies of the NaI−ScI 3 system have also been reported. , In addition, Hilpert 6 has reviewed much of the information on complexation of metal halide vapors.…”
Section: Introductionmentioning
confidence: 70%
“…Separate mass spectra on NaBr vapor show that the intensities of Na + and NaBr + are very similar, so that Na + is a major fragment ion from NaDyBr 4 , as seen also in NaScI 4 vapor. 4,5 Intensities of the principal ions NaBr + , DyBr 3 + , and NaDy-Br 3 + were then measured at AE + 3 eV at a series of temperatures. From the mass spectra of NaBr, DyBr 3 , and that of NaBr-DyBr 3 reported here, the fragmentation patterns of each of the gaseous neutrals NaBr, DyBr 3 , and NaDyBr 4 in the mixture were sorted out so that the total ion yields of each at AE + 3 eV could be evaluated from the intensities of the principal ions noted above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The instrumentation constant was calculated from the observed NaC1 vaporization data. The ionization cross section of molecules was calculated from the sum of atomic ionization cross sections (Hildenbrand et al, 1990). The atomic ionization cross-section data were taken from the compilation by Mann (1967).…”
Section: ?mentioning
confidence: 99%